2014
DOI: 10.1063/1.4904884
|View full text |Cite
|
Sign up to set email alerts
|

Anisotropy of band gap absorption in TlGaSe2 semiconductor by ferroelectric phase transformation

Abstract: The depth-resolved free-carrier absorption and the photo-acoustic response are used to examine the band-gap absorption in 2D-TlGaSe2 layered semiconductor after its transformation into the ferroelectric F-phase below 107 K. The absorption exhibits unusual behavior with a biaxial character in respect to the light polarization on the layer plane. A spectral analysis shows that the anisotropy is associated to the lowest Γ-direct optical transition. The Γ-absorption and the localized exciton at 2.11 eV are dipole-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
14
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
4

Relationship

2
2

Authors

Journals

citations
Cited by 4 publications
(14 citation statements)
references
References 25 publications
0
14
0
Order By: Relevance
“…This is a kind of hybridization of electron lone pairs. [8,9,11] Such excess carrier separation does not exist in isotropic semiconductor crystals. The crystal phase transition by the use of light can be simply understood as a minimization of the potential energy by a sufficiently strong separation of e-h pairs.…”
Section: Model Of Spontaneously Polarized Layered Crystalmentioning
confidence: 99%
See 2 more Smart Citations
“…This is a kind of hybridization of electron lone pairs. [8,9,11] Such excess carrier separation does not exist in isotropic semiconductor crystals. The crystal phase transition by the use of light can be simply understood as a minimization of the potential energy by a sufficiently strong separation of e-h pairs.…”
Section: Model Of Spontaneously Polarized Layered Crystalmentioning
confidence: 99%
“…On cooling the TlInS 2 crystal loses inversion center undergoing two sequential transitions via incommensurate I-phase into ferroelectric F-phases. Tl + ion deviation and grouping occurs in the interlayer [8,9] and the I-phase is accompanied by strong resonance of complex dielectric function. [10] The lattice unit quadrupling within I-phase occurs around 200 K. [5] Weakness of interlayer bonds results from the sp-hybridization of the Tl electrons wave function where a strong coupling among the spins of Tl and In metal ions on neighboring layers is observed.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The unit cell contains 16 atoms positioned on two adjacent layers rotated by 90° angle in (100) plain. The Tl atoms lie in perpendicular trigonal cavities between layers and provide a weak interlayer covalent bonding [1,[3][4][5][6][7]. Due to the sufficient length of these bonds, there is a predisposition for electrical anisotropy.…”
Section: Introductionmentioning
confidence: 99%
“…In recent years, TlGaSe 2 and TlInS 2 compounds have gained significant interest because of discovering their unique, unexpected electro-optical properties. In conjunction with previously known sequential phase transitions occurring at low temperatures, extensively studied during last decades [1,3,4], recent investigation indicated electro-optical metastable transformations if samples were thermo-cycled or kept for a certain period in the external electric fields (see [5] and references therein). Our previous works have shown that Tl-GaSe 2 as well as the equivalent TlInS 2 compound obey phenomena of temporal or permanent photo-darkening (giant Stark effect) after a prolonged intense laser pulse irradiation [6,7].…”
Section: Introductionmentioning
confidence: 99%